"A Collection of Stories, Poetry and Theories": Homelessness, Outsider Memoirs, and the Right to Theorize. Issue 2 (3rd July 2019) - Speer, Jessie
Abstract : This paper argues that memoirs of homelessness advance a form of social theory that emerges from the lived experience of homelessness and housing displacement. While scholars have called for greater recognition of previously neglected forms of social theory, academic scholarship remains—in practice—overwhelmingly influenced by the theories of a narrow group of high-profile intellectuals and specialist textual forms. Life narratives, in particular, have often been framed as atheoretical testimonies, and homeless thinkers have been largely denied the right to theorize. This paper argues that reading "outsider memoirs" as theoretical texts can be a method for expanding current understandings of the nature of social theory and taking seriously the epistemic rights of marginalized thinkers. It engages with the writings of homeless memoirists to argue for a new understanding of the explanatory power of social theory that does not collapse into abstraction or generalization, but is profoundly rooted in reflection and collaboration.